Penggunaan Daging Keong Mas (Pomacea caniculata) terhadap Kualitas Kerupuk - Choiroel Anam (Caraka Tani: Journal of Sustainable Agriculture, 2005)
Research about chips made from flour falvored with gold snail has been conducted to know the characteristic of physical, chemical and organoleptic chips results. Data were analyzed with Completely Randomized Design (CRD) by single factor. The factor is ratio between tapioca flour and gold snail meat.The result show that adding snail meat at batter chips was increasing content of water, protein, ash and taste. In other side decreasing content of strach, will reduce the development and color of chips. Chemical, physical and organoleptic examination showed best result at 30% of gold snail meat as substitution at chip.